KARAKTERISTIK KONSUMEN DALAM PEMBELIAN DAGING AYAM FROZEN DI TOKO PRIMA FRESHMART KECAMATAN KEMILING KOTA BANDAR LAMPUNG - Herwansyah, Trio; Unteawati, Bina; Kusmaria, Kusmaria; Handayani, Sri (Program Studi Pengelolaan Agribisnis, 2025)
Prima Freshmart, as a store that provides frozen food products, especially frozen chicken meat, faces challenges in optimally meeting the needs and preferences of its customers. Consumers who visit Prima Freshmart have diverse demographic backgrounds and purchasing behaviors, which influence their buying decisions and purchase frequency. This study aims to analyze the characteristics of consumers purchasing frozen chicken meat at Prima Freshmart. A sample of 35 respondents was taken using accidental sampling. Data collection was conducted through interviews assisted by questionnaires. Descriptive analysis was used in this study. The results show that the majority of consumers are females aged 21-29 years, with education ranging from senior high school to undergraduate level, married, earning between Rp2–5 million, and working as entrepreneurs. Purchases are usually made twice a week, with variations ranging from daily to monthly.